Expression of unique chimeric human papilloma virus type 16 (HPV‐16) L1‐L2 proteins in Pichia pastoris and Hansenula polymorpha. Issue 9 (24th May 2018) - Bredell, Helba; Smith, Jacques J.; Görgens, Johann F.; van Zyl, Willem H.
Abstract: Cervical cancer is ranked the fourth most common cancer in women worldwide. Despite two prophylactic vaccines being commercially available, they are unaffordable for most women in developing countries. We compared the optimized expression of monomers of the unique HPV type 16 L1‐L2 chimeric protein (SAF) in two yeast strains of Pichia pastoris, KM71 (Mut s ) and GS115 (Mut + ), with Hansenula polymorpha NCYC 495 to determine the preferred host in bioreactors. SAF was uniquely created by replacing the h4 helix of the HPV‐16 capsid L1 protein with an L2 peptide. Two different feeding strategies in fed‐batch cultures of P. pastoris Mut s were evaluated: a predetermined feed rate vs. feeding based on the oxygen consumption by maintaining constant dissolved oxygen levels (DO stat). All cultures showed a significant increase in biomass when methanol was fed using the DO stat method. In P. pastoris the SAF concentrations were higher in the Mut s strains than in the Mut + strains. However, H. polymorpha produced the highest level of SAF at 132.10 mg L −1 culture while P. pastoris Mut s only produced 23.61 mg L −1 . H. polymorpha showed greater potential for the expression of HPV‐16 L1/L2 chimeric proteins despite the track record of P. pastoris as a high‐level producer of heterologous proteins.